How can regional policy help address climate impacts in agriculture? Evaluating the climate-smart agriculture strategy for Central America (EASAC) - Howland, Fanny; Le Coq, Jean-francois; Collazos, Sara; Arana, Jose; Blundo, Genowefa; Castellanos, Andrea; Martinez Baron, Deissy (Informa UK Limited, 2024)
The design and implementation of targeted policies and programmes are crucial to addressing climate challenges. In this study, we sought to understand the means by and extent to which the Central American Climate-Smart Agriculture Strategy (EASAC) has contributed to addressing the specific climate challenges facing the regional agricultural sector. We applied a theory-based evaluation and contribution analysis to examine this policy and identified 252 changes at the national and regional levels that align with the EASAC theory of change (ToC). Contribution analysis revealed that none of the 23 changes we assessed could be attributed solely to the EASAC; however, it contributed directly, in combination with other actors and institutions, to 10 such changes. Our results question the efficacy of non-binding regional policies, such as the EASAC, in influencing national policy changes and highlight the dependency of climate policy implementation on international cooperation in the Central American Integration System region. Intersectoral and actor coordination, the availability of technical and research expertise, and research input appear critical to the successful implementation of regional climate policy.